(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article focuses on enhancing academic offerings by managing the development of communicative competence in college students. The strategies proposed include integrating communicative competence into course content, providing professional development for faculty, offering language learning support services, incorporating real-world communication opportunities, and implementing assessment and feedback mechanisms. These strategies aim to prepare students for success in their academic pursuits and future careers by enhancing their oral and written communication skills, intercultural communication abilities, and effective language use within specific academic disciplines.